Effect of fertilizer management on productivity of potato-hybrid maize intercropping system - Begum, AA; Bhuiya, MSU; Hossain, SMA; Khatun, Amina; Das, SK (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at the research field of Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during 2011-12 to find out proper combination of fertilizer nutrients of potato hybrid maize intercropping system for higher productivity and economic return. Ten fertilizer dose viz., F1= Control (without fertilizer), F2=260P72K148S48Zn4B2 (100% recommended fertilizer, RF for hybrid maize HM), F3=N180P40K180S20Zn4B1.2 (100% RF for potato), F4=N440P112K328S68Zn6B2 (100% RF for HM + 100% RF for potato), F5=N352P90K262S54Zn6B2 (80% RF for HM + 80% RF for potato), F6=N395P102K283S63Zn6B2 (100% RF for HM + 75% RF for potato), F7=N350P92K238S58Zn6B2 (100% RF for HM + 50% RF for potato), F8= N375P94K291S56Zn6B2 (100% RF for potato + 75% RF for HM), F9=N310P76K254S44Zn6B2 (100% RF for potato + 50% RF for HM) and F10=N320P73K170S50Zn6B2 kg ha-1 (BARI RF for potato hybrid maize intercropping) were tested on potato hybrid maize intercropping system. BARI Alu-8 (Cardinal) variety of potato and BARI Hybrid maize-7 variety of hybrid maize were used in this study. Maximum photosynthetically active radiation interception, leaf area index and total dry matter production of intercropped potato and maize were observed at the highest fertilizer level N440P112K328S68Zn6B2 kg ha-1 (100% RF for HM + 100% RF for potato). The highest tuber yield of potato (30.20 t ha-1) and grain yield of maize (9.48 t ha-1) were observed from fertilizer dose of N375P94K291S56Zn6B2 (100% RF for potato + 75% RF for HM). The highest potato equivalent yield (40.47 t ha-1), gross return (Tk.526110 ha-1), gross margin (Tk. 381957 ha-1) and benefit cost ratio (3.65) were also observed from the same fertilizer rate. The results revealed that fertilizer dose of N375P94K291S56Zn6B2 kg ha-1 (100% RF for potato + 75% RF for HM) might be economically profitable for potato hybrid maize intercropping system. Bangladesh J. Agril. Res. 41(4): 633-645, December 2016